Learning outcomes of nursing curriculum in Turkey: a cross-sectional study - Mersin Sevinç; Saray Kılıç Hülya; İbrahimoğlu Özlem (Sciendo, 2020)
To assess the nursing curriculum and point out learning outcomes in Turkey.